Examining SPeCTRUM as an e-learning platform to empower students' learning among five faculties in University of Malaya - Ghavifekr, Simin; Sulaiman, Abdul Halim; Danaee, Mahmoud; Ng, Siew Cheok; Adewale, Adebayo Saheed (2017)
This study alms at examining SPcCTRUM to empower students' learning among five faculties(Business & Accountancy, Education, Engineering, Medicine and Science) in UM. The study used a quantitative research design and the data were analyzed using both descriptive and Inferential statistical methods to define the relationship between the variables. The population of the study comprises of undergraduate and Master students from the five selected faculties In University of Malaya and random sampling technique was used to select the respondents. This gives every member of the population equal chance of being selected. A total of 750 questionnaires were distributed to students over a period of 2 months across the selected faculties. Out of these, 541 were returned. The research Instrument for this study is a combination of adapted and self-developed survey questionnaire, consists of nine sections of A to I consisting; Demographic Information, Self-Efflcacy, Attitude, Perceived value, Behavioral intention, Faci litating condition, Skills and knowledge, Challenges and barriers and Usage pattern of SPeCTRUM among the students of University of Malaya. Pearson correlation coefficient, Independent sample T-Test and Two-way Analysis of Variance were used In analyzing the result gathered from the respondents In the study. The result shows that there exists significant relationship between demographic Information in relation to level and pattern of SPeCTRUM usage and learn Ins outcome of students In the five selected faculties In UM. Also, there Is a positive relationship between SPeCTRUM usage and students learning outcome In the five faculties. In addition, the level of students' skills, knowledge, attitude, perceived platform more functional and responsive to needs of students, staff and university there is need to enhance the usage among staffs and students in University of Malaya.